Competition between humic substances and α-amino acids by metal species - Dos Santos, Ademir [UNESP]; Bellin, Iramaia C. [UNESP]; Corbi, Pedro Paulo [UNESP]; Cuin, Alexandre [UNESP]; Rosa, André Henrique [UNESP]; Rezende, Maria Olimpia de O.; Rocha, Julio Cesar [UNESP]; Melnikov, Petr (FapUNIFESP (SciELO), 2004)
The aim of the present work was to carry out experimental comparison between humic substances (HS) and representative α-amino acids (methionine, methionine sulfoxide and cysteine hydrochloride) in relation to the complexation of biologically active trace elements (Al, Cu, Pb, Mn, Zn, Cd and Ni). A mobile time-controlled tangential-flow UF technique was applied to differentiate between HS-metal and α-aminoacids-metal complexes. Metal determinations were conventionally carried out using a ICP-OES. The results showed that HS may be considered as a selective complexing agents with higher metal bonding capability in relation to Al, Cu and Pb, the fact that may be clinically important.
Keywords: α-amino acids; Humic substances; Metals; Soils; alpha amino acid; aluminum; cadmium; copper; cysteine; lead; manganese; metal; methionine; methionine sulfoxide; nickel; trace element; zinc; chemical bond; flow; humic substance; inductively coupled plasma optical emission spectrometry; spectrometry; time; ultrafiltration